Diagnostic value of magnetic resonance neurography in cervical radiculopathy: plexus patterns and peripheral nerve lesions - Schwarz, Daniel; Kele, Henrich; Kronlage, Moritz; Godel, Tim; Hilgenfeld, Tim; Bendszus, Martin; Bäumer, Philipp (Investigative radiology, 2018)
ObjectiveThe aim of this study was to assess the imaging appearance and diagnostic value of plexus and peripheral nerve magnetic resonance neurography (MRN) in cervical radiculopathy.Materials and MethodsThis prospective study was approved by our institutional ethics committee and written informed c
Gesehen am 03.09.2019